KAJIAN EKSPERIMENTAL POLA RETAK PADA SAMBUNGAN BALOK-KOLOM BETON PRACETAK DENGAN MENGGUNAKAN SAMBUNGAN KERING - Cahyani, Kharisma Nur (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
There is a major problem in the installation of precast concrete system, namely connection. Connection on precast system must have strength that can withstand the loads that occur. One of the system used in precast concrete connection is by using dry connection method. Dry connection is a connection between precast concrete element using a steel plate as a connector, which is bolted or welded. Judging from the connection problems in precast concrete, a study was conducted to observed the behavior of precast beam-column connection observations are also made to analyze a collapse model, and a crack pattern between the joints of the beam-column precast. Keywords: precast concrete, dry connection, collapse model, crack pattern